2015
DOI: 10.3402/gha.v8.29553
|View full text |Cite
|
Sign up to set email alerts
|

Do the pre-service education programmes for midwives in India prepare confident ‘registered midwives’? A survey from India

Abstract: ObjectiveThe graduates of the diploma and degree programmes of nursing and midwifery in India are considered skilled birth attendants (SBAs). This paper aimed to assess the confidence of final-year students from pre-service education programmes (diploma and bachelor's) in selected midwifery skills from the list of midwifery competencies of the International Confederation of Midwives (ICM).DesignA cross-sectional survey was conducted in Gujarat, India, involving 633 final-year students from 25 educational insti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
49
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 37 publications
(52 citation statements)
references
References 26 publications
(27 reference statements)
3
49
0
Order By: Relevance
“…The results showed that one third to one fourth of the students in the present study scored high on confidence in the three domains. This is quite similar to the findings from India, where Sharma and co-authors [13] found that 23-28% scored above the 75 th percentile.…”
Section: High Levels Of Confidencesupporting
confidence: 89%
See 2 more Smart Citations
“…The results showed that one third to one fourth of the students in the present study scored high on confidence in the three domains. This is quite similar to the findings from India, where Sharma and co-authors [13] found that 23-28% scored above the 75 th percentile.…”
Section: High Levels Of Confidencesupporting
confidence: 89%
“…Nevertheless, the multi-country approach and the large number of respondents make the data reliable. The questionnaire has been used in other studies [13,22,27], and further developed and refined by a group of senior researchers for the current study. This strengthen the validity of the tool.…”
Section: Age and Sexmentioning
confidence: 99%
See 1 more Smart Citation
“…These interviews and evidence reported elsewhere reinforce the urgent need to improve midwifery and nursing education [26,29,[37][38] .…”
Section: Discussionmentioning
confidence: 62%
“… 18 An Indian study indicated that final year midwifery students had low level of confidence in basic midwifery competencies for antepartum, intrapartum, postpartum, and newborn care. 19 The State of the World’s Midwifery Report 2014 covering 73 low- and middle-income countries also found pervasive gaps in midwifery education. 8…”
Section: Discussionmentioning
confidence: 99%